RELATIONSHIP BETWEEN INOCULATION METHODS ON SWEET PEPPER’S SEEDS INFECTION BY Clavibacter michiganensis subsp. michiganensis CAUSED BY BACTERIAL CANKER - Bogo, Amauri; Takatsu, Armando; Boff, Mari Inês C.; Amarante, Cassandro V. T. do (Revista de Ciências Agroveterinárias, 2002)
Seed infection of sweet pepper by bacterial canker (Clavibacter michiganensis subsp. michiganensis) were induced by different methods of inoculation: a) spraying of flowers with bacterial suspension; b) prick inoculation of pedicel tip of small fruits with needle through a droplet of bacterial suspension; c) prick inoculation of stem through a droplet of bacterial suspension deposited at the insertions of first pair of permanent leaves and d) by methods “a” and “b”. All the inoculation methods produced infected seed with or without visual symptons, with the infection in pericarp, endosperm and embryo. When flowers were inoculated by spraying of flowers, the pathogenic bacteria seemed to invade seeds through calyx scar and vascular bundle. Infection through this route was suggested to occur in field when the disease become epidemic. The selection of seeds through visual sanity aspect is not trustful parameter because the bacteria can be transmitted by symptomless seeds.